If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x+(-4-9)=6
We simplify the equation to the form, which is simple to understand
-5x+(-4-9)=6
Remove unnecessary parentheses
-5x-13=+6
We move all terms containing x to the left and all other terms to the right.
-5x=+6+13
We simplify left and right side of the equation.
-5x=+19
We divide both sides of the equation by -5 to get x.
x=-3.8
| -5p=2p-35 | | 2(6-x)=2 | | -14+x=-32 | | (x-6y)(5x+6y)=0 | | 3y+x=0 | | (8x-3)-(4x-8)= | | 5x-25=2(2x+3) | | -3-3y=-15x | | y+1=3(0-2) | | 35-x=-8-3(1+8x) | | 3x+2=5x-24 | | 17=4(a-2)+2 | | 6*g=9 | | 2x^2+27x-8.7=0 | | Y-2-x=0 | | 32x+32=27x | | -11-3x=10-4x | | 4(8-x)=16 | | 5x-(2.2x+8)= | | 74/22200= | | -6=2h-10 | | 8-0(9+0)= | | -5+8=72 | | m-3.41=10.7 | | 3=-y | | Y-3=3.2(x-1) | | 22200/74= | | -18+24+(-13)+(-19)= | | -3y+3x=6 | | -2y-2x=14 | | 5x-17=-52 | | 7z=18-25 |